A framework and decision support tool for improving value chain resilience to critical materials in manufacturing. Issue 1 (1st January 2018) - Gardner, Liam; Colwill, James
Abstract: Certain non-energy materials have been identified as being critical to the manufacturing sector and wider economy due to having a high risk of supply disruption combined with high economic importance. The criticality of specific raw materials is becoming increasingly acute as the escalating use of resources is driven by an increasing global population. Critical materials are vital elements in the value chain yet their supply risk may often be ineffectively addressed by traditional supply chain management strategies. Most research to date has been focused at a national or industrial policy level thus many manufacturers are unaware if their operations are at risk from critical materials at a product level. This paper presents a framework that takes a systematic approach to identifying, assessing and mitigating risk associated with critical materials bilaterally along the value chain to facilitate manufacturers in the identification, assessment and mitigation of critical material supply risk. This paper also describes how the framework can be facilitated for application in industry through preliminary design specifications towards a development of a decision support tool.